(untitled) (GIST – Education and Learning Research Journal, 2020)
This study aimed at investigating EFL pre-service teachers’ attitudes toward pronunciation and pronunciation teaching. Another purpose was to explore the outcomes of pronunciation instruction on EFL pre-service teachers’ phonological development and based on the findings to provide suggestions taking learners’ pedagogical needs into consideration. The study was conducted using a quantitative research design method. 107 EFL pre-service teachers participated in the study. The quantitative instruments were Pronunciation Attitude Inventory, pre and post period of the intervention. During one term, the researcher provided EFL pre-service teachers with pronunciation instruction focusing on segmental and suprasegmental features in English pronunciation. Pre- and post-tests were used to measure to what extent language learners improved their pronunciation in English using a reading passage and participants’ performances were recorded through a tape recorder. The administration of the inventory took place at the end of the semester and the participants were asked to read and respond the whole inventory in 15 minutes. After completing data collection process, two native speakers of English as the raters of the study rated all the participants’ pre-test and post-test performances one by one. A pronunciation rubric which involves 5 categories including vowels, consonants, intonation, word-stress and comprehensibility was used in order to assess learners’ performances. The results revealed that the participants had generally positive attitudes toward pronunciation. Similarly, it was found that pronunciation instruction improved the participants’ pronunciation at the segmental and suprasegmental levels as well as their comprehensibility.